The principles of maintaining cleanliness and order in communities according to court decisions - Jabłoński, Maciej (Studia Ecologiae et Bioethicae, 2013)
The maintenance of cleanliness and order in communities is the responsibility of the municipality as the basic unit of local government in Poland. The municipality performs its role in the field of environmental protection according to a range of legal provisions. Changing regulations affect the application of the law of cleanliness and order in communities, leaving it open to interpretation. A key guide in this regard is the wealth of court decisions on cleanliness and order in communities and waste management.